The effect of exercise and physical activity-interventions on step count and intensity level in individuals with multiple sclerosis: a systematic review and meta-analysis of randomized controlled trials - Arntzen, Ellen Christin; Bidhendi-Yarandi, Razieh; Sivertsen, Marianne; Knutsen, Karina; Dahl, Stine Susanne Haakonsen; Hartvedt, Maria Grytvik; Normann, Britt; Behboudi-Gandevani, Samira (Frontiers in Sports and Active Living, 2023)
Background: Reduced physical activity is a worldwide challenge in individuals with multiple sclerosis (MS). The aim of this systematic review and meta-analysis was to identify devise-measured effects of physical activity, exercise and physiotherapy-interventions on step count and intensity level of physical activity in individuals with MS. Methods: A systematic search of the databases of PubMed (including Medline), Scopus, CINHAL and Web of Science was carried out to retrieve studies published in the English language from the inception to the first of May 2023. All trials concerning the effectiveness of different types of exercise on step count and intensity level in people with MS were included. Results: A total of 8 randomized clinical trials (involving 919 individuals with MS) were included. The participants (including 715 (77.8%) female and 204 (22.2%) male) had been randomly assigned to the Intervention (n = 493) or Control group (n = 426). In terms of the comparison within the Intervention and the Control groups before and after the intervention, the results of the meta-analysis indicate that the pooled standardized mean difference (SMD) for step-count in the Intervention group was 0.56 (95% CI: -0.42, 1.54), while in the Control group it was 0.12 (95% CI: -0.05, 0.28). Furthermore, there was no significant difference in the pooled SMD of step-count in the physical activity Intervention group compared to the Controls after the intervention (pooled standard mean difference = 0.19, 95% CI: -0.36,0.74). Subgroup analysis on moderate to vigorous intensity level of physical activity revealed no significant effect of the physical activity intervention in the Intervention group compared to the Control group after the intervention, or within groups before and after the intervention. Results of meta-regression showed that age, BMI, duration of disease and Expanded Disability Status Scale (EDSS) score were not the potential sources of heterogeneity (all p > 0.05). Data on the potential harms of the interventions were limited. Conclusion: The results showed no significant differences in step count and moderate to vigorous physical activity level among individuals with MS, both within and between groups receiving physical activity interventions. More studies that objectively measure physical-activity are needed.